Spontaneous precipitation pattern formation by crystallites of Mn–Fe-based Prussian blue analogues in agarose gel. Issue 62 (7th November 2019) - Hayashi, Hisashi; Aoki, Saya; Suzuki, Tomoko
Abstract : Precipitation patterns spontaneously formed by Mn–Fe PBAs in agarose gel were investigated over wide concentrations ranges for the outer (0.10 ≤ [Mn 2+ ] ≤ 0.70 M) and inner electrolytes (0.01 ≤ [[Fe(CN)6 ] 3− ] ≤ 0.35 M) by visual/SEM observations. Abstract : Precipitation patterns spontaneously formed by Mn–Fe-based Prussian blue analogues (Mn–Fe PBAs) in agarose gel were investigated over wide concentration ranges for the outer (0.10 ≤ [Mn 2+ ] ≤ 0.70 M) and inner electrolytes (0.01 ≤ [[Fe(CN)6 ] 3− ] ≤ 0.35 M). The precipitation patterns were classified into five types: continuous in the inner electrolyte gel, continuous in the outer electrolyte gel, a very short band close to the gel boundary, periodic bands in the inner electrolyte gel, and filament-like patterns in the inner electrolyte gel. The concentrations found to be suitable for applications as pulsatile 137 Cs adsorbent delivery materials, for which the periodic patterns were most distinct and frequently occurring, were [Mn 2+ ] ≈ 0.55 M and [[Fe(CN)6 ] 3− ] ≈ 0.10 M. The filament-like pattern, reported here for the first time, was generated near the cylindrical gel surface in a local, stochastic, and two-dimensional manner. Scanning electron microscopy (SEM) images of the periodic band patterns indicate that the Mn–Fe PBA precipitates in periodic patterns consist of cubic crystallites (3–10 μm, each side), suggesting significant contributions from Ostwald ripening to the precipitation process. In contrast, precipitates in the filament-like pattern consist of relatively smaller cubic crystallites (≲1 μm, each side), implying an important role of rapid nucleation in the formation of this structure. SEM observations also suggest that, overall, agarose gels support crystallite ripening more effectively, and hence also better suppress the formation of definite periodic bands, than water-glass gels. These findings provide useful information for future applications of self-assembled Mn–Fe PBA patterns in gels.